1986
DOI: 10.2527/jas1986.62142x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Behavior of Beef Cows at Parturition

Abstract: Over an 11-yr period maternal behavior, calf birth weight and calf condition were recorded within 24 h for 2,684 parturitions. Maternal behavior was rated on a scale from 1 to 11, where 1 indicated extreme aggressiveness and 11 indicated no maternal attentiveness. Birth condition was rated on a scale from 1 to 9, with 9 being fattest and 1 thinnest. Respective breed means of Hereford, Angus, Charolais and Red POll were 6.2, 5.3, 6.0, and 5.7 for maternal behavior rating; 30.6, 27.3, 39.2 and 32.6 kg for birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2
12

Year Published

1993
1993
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 7 publications
4
23
2
12
Order By: Relevance
“…The genetic component of maternal aggressiveness in beef cattle reported by Buddenberg et al (1986) and Morris et al (1994), although significantly different from zero and possibly underestimated as a result of frequent handling, is lower than that reported for other temperament traits measured in non-lactating cattle. These traits, which include response to isolation, flight distance, restlessness in the crush and flight speed from the crush have a mean heritability of 0.36 when measured in unrestrained conditions and 0.23 when the animal is held in a crush (Burrow, 1997).…”
Section: Heritability and Repeatabilitycontrasting
confidence: 65%
See 4 more Smart Citations
“…The genetic component of maternal aggressiveness in beef cattle reported by Buddenberg et al (1986) and Morris et al (1994), although significantly different from zero and possibly underestimated as a result of frequent handling, is lower than that reported for other temperament traits measured in non-lactating cattle. These traits, which include response to isolation, flight distance, restlessness in the crush and flight speed from the crush have a mean heritability of 0.36 when measured in unrestrained conditions and 0.23 when the animal is held in a crush (Burrow, 1997).…”
Section: Heritability and Repeatabilitycontrasting
confidence: 65%
“…A heritability of 0.09 (S.E. 0.03) for a maternal responsiveness score, measured when tagging calves within 24 h of birth on a similar scale to that of Buddenberg et al (1986), was reported by Morris et al (1994) using several purebred beef and beef cross dairy breeds. In this study, a total of 2121 cows were observed over a mean of 2.8 parturitions each, and the repeatability across parturitions was 0.20.…”
Section: Heritability and Repeatabilitymentioning
confidence: 80%
See 3 more Smart Citations